2004
DOI: 10.1177/229255030401200401
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Capsular Contracture in 319 Consecutive Augmentation Mammaplasties: Dependent Drains As A-Possible-Factor

Abstract: N Fanous, I Salem, C Tawilé, AE Bassas. Absence of capsular contracture in 319 consecutive augmentation mammaplasties: Dependent drains as a possible factor. Can J Plast Surg 2004;12(4):193-197. Capsular contracture is one of the major complications of augmentation mammaplasty. A review of 638 augmented breasts in 319 consecutive patients who underwent primary augmentation, with an average follow-up of 17.2 months and without a single case of capsular contracture of any degree to date, is presented, along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…In a 2004 study by Fanous et al., a retrospective review of 319 patients was performed, all of which had placement of an eight French suction drain for 24 hours postoperatively. Although their goal of no capsular contractions was met, they also noted a 0% incidence of implant infection [24]. Two years later, a larger retrospective review of 502 patients demonstrated similar findings.…”
Section: Non‐urologic Literature Supporting the Use Of Closed‐suctionmentioning
confidence: 76%
“…In a 2004 study by Fanous et al., a retrospective review of 319 patients was performed, all of which had placement of an eight French suction drain for 24 hours postoperatively. Although their goal of no capsular contractions was met, they also noted a 0% incidence of implant infection [24]. Two years later, a larger retrospective review of 502 patients demonstrated similar findings.…”
Section: Non‐urologic Literature Supporting the Use Of Closed‐suctionmentioning
confidence: 76%
“…The amount of irrigant used was less than what was reported in previous literature. 9 Similar techniques for reducing CC were discussed by Rohrich et al 39 In another study, Fanous et al 40 theorized that their decreased CC rate was due to postoperative drains, but they used breast pocket irrigation with antimicrobial solutions as well. Recent findings from a porcine model study demonstrated protection against subclinical implant infection and CC from antibiotic-impregnated mesh placed at the time of surgical insertion.…”
Section: Discussionmentioning
confidence: 94%
“…Proponents of CSD often cite non-urologic literature in which surgeries such as breast implants [9], hepatectomy [10], and others use drainage systems. Despite fears to the contrary, there was no evidence of increased infection rate with CSD use in breast reconstructive surgery [11].…”
Section: The Case For Csd Usementioning
confidence: 99%